Herbaceous ground flora inventory of a permanent biomon plot in a lowland rainforest of Mt. Makiling - Pizaña, Shyrelle Therese P. 1977- (2004)
A floristiv inventory of ground herb species was conducted in the 1-ha BioMon plot located in Mt. Makiling with an elevation range of 230-270m...
"August 2004."
Thesis (M.S. Biology )--University of the Philippines Diliman.
Keywords: Herbaceous plants -- Philippines -- Mount Makiling (Los Baños, Laguna).